2009
DOI: 10.1371/journal.pone.0005140
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sampling in One Day to Optimize Smear Microscopy in Children with Tuberculosis in Yemen

Abstract: Background and AimThe diagnosis of pulmonary Tuberculosis (TB) in children is difficult and often requires hospitalization. We explored whether the yield of specimens collected for smear microscopy from different anatomical sites in one visit is comparable to the yield of specimens collected from a single anatomical site over several days.Methodology and Principal FindingsChildren with signs/symptoms of pulmonary TB attending a reference hospital in Sana'a Yemen underwent one nasopharyngeal aspirate (NPA) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 8 publications
2
36
0
Order By: Relevance
“…36,40 Multiple specimens are helpful at achieving the maximum yield. 16,38,41 Urine tests for mycobacterial lipoarabinomannan by both ELISA and lateral flow were reported to be sensitive in adults with advanced HIV disease, but had low sensitivity and specificity in children. 42,43 …”
Section: Review and Discussionmentioning
confidence: 99%
“…36,40 Multiple specimens are helpful at achieving the maximum yield. 16,38,41 Urine tests for mycobacterial lipoarabinomannan by both ELISA and lateral flow were reported to be sensitive in adults with advanced HIV disease, but had low sensitivity and specificity in children. 42,43 …”
Section: Review and Discussionmentioning
confidence: 99%
“…Al-Aghbari et al [20], reported that the combined yield of single expectorated sputum, NPA, SI and GA specimens was similar to the yield of specimens collected over consecutive days (e.g. three GA).…”
Section: Why Is Childhood Tb Not Considered a Major Public Health Promentioning
confidence: 90%
“…Initial studies reported that NPA had better sensitivity than IS [18] and similar yield to GA [19]. However, later studies in Yemen [20] and Peru [21] have suggested that the method has a lower yield. The few studies available however have included a wide range of settings, from reference hospitals to community-based populations, and these findings may reflect a differential yield for children with mild and severe illnesses.…”
Section: Why Is Childhood Tb Not Considered a Major Public Health Promentioning
confidence: 99%
“…According to the WHO and IULTD recommendations, the use of BAL or sputum induction for the diagnosis of TB is only justified if the patient is unable to produce sufficient sputum for examination, or when 2-3 high quality early morning sputum samples have been smear negative and a high index of suspicion of pulmonary TB persists [7][8][9][10][11][12]. Gastric lavage is appropriate in children under 5 who are unable to produce sputum reliably [9,13,14]. Some centers have used induced sputum [10], naso-pharyngeal aspiration [15], BAL [16] or a combination of BAL and GL [17] in children with varying degrees of success.…”
Section: Discussionmentioning
confidence: 99%